A 3D nanostructure of graphene interconnected with hollow carbon spheres for high performance lithium–sulfur batteries1. Issue 21 (7th June 2015) - Liu, Shuangke; Xie, Kai; Chen, Zhongxue; Li, Yujie; Hong, Xiaobin; Xu, Jing; Zhou, Liangjun; Yuan, Junfei; Zheng, Chunman
<x xml:space="preserve">Abstract</x> A novel 3D rGO–HCS nanostructure was designed via a hydrothermal self-assembly method. When used as a sulfur cathode, it delivers a low capacity-decay rate of 0.052% per cycle after 400 cycles and shows a high rate performance.